2013
DOI: 10.1007/s10384-012-0226-4
|View full text |Cite
|
Sign up to set email alerts
|

Dry eye and tear film functions in patients with psoriasis

Abstract: The dry eye symptom was more common in patients with psoriasis. In addition, the patients showed a higher tear film instability and significant degeneration on the ocular surface when compared with the normal controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 31 publications
5
32
2
Order By: Relevance
“…frequency of replacement, type of cleaning solutions) affect dry eye symptoms. Other factors such as environmental conditions [3, 4, 3841], stress levels [34] and autoimmune diseases [34, 42, 43] were not included.…”
Section: Discussionmentioning
confidence: 99%
“…frequency of replacement, type of cleaning solutions) affect dry eye symptoms. Other factors such as environmental conditions [3, 4, 3841], stress levels [34] and autoimmune diseases [34, 42, 43] were not included.…”
Section: Discussionmentioning
confidence: 99%
“…10 Besides the known systemic findings, the ocular involvement includes inflammation of the eyelids, conjunctiva, cornea, lachrymal glands, and the uvea. [11][12][13][14] Her et al 15 reported that dry eye in patients with psoriasis is common, and the tear film is relatively unstable with ocular surface damage compared with normal controls. 11,12 Punctate keratitis was frequently reported.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular comorbidity was reported in 10-15% of patients with plaque psoriasis, but such data is likely to be underestimated. Ocular diseases most frequently found in patients with psoriasis are seborrheic blepharitis that may progress toward madarosis, ectropion, entropion, anterior uveitis, and dry eye syndrome (1,22,23). Treatment of this comorbidity has not been defined yet.…”
Section: Secukinumab Treatment In Psoriatic Patients: Italian Experiementioning
confidence: 99%